2000
DOI: 10.1046/j.1365-294x.2000.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary separation of sympatric carnivores identified by molecular analysis of scats

Abstract: We studied the diets of four sympatric carnivores in the flooding savannas of western Venezuela by analysing predator DNA and prey remains in faeces. DNA was isolated and a portion of the cytochrome b gene of the mitochondrial genome amplified and sequenced from 20 of 34 scats. Species were diagnosed by comparing the resulting sequences to reference sequences generated from the blood of puma (Puma concolor), jaguar (Panthera onca), ocelot (Leopardus pardalus) and crab-eating fox (Cerdocyon thous). Scat size ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
304
2
9

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(328 citation statements)
references
References 33 publications
(35 reference statements)
7
304
2
9
Order By: Relevance
“…However, in this study we had similarly high success rates for DNA extraction and PCR amplification for species, sex and individual identification from jaguar faecal samples in two areas with contrasting environmental conditions. Furthermore, species identification rates based on our previously developed method (Roques et al, 2011) were higher (70% for Serra da Capivara National Park and 81% for Caiman Ecological Refuge) than those reported for sequencing methods for faeces of the same species collected in the field (59%, Farrell et al, 2000;55%, Haag et al, 2009). The use of a single pair of Amelogenin-based primers for sex determination also proved to be reliable and a more efficient technique (73-96% success rates) than those previously reported, which were usually based on amplification of the Y-chromosome-linked sexdetermining region gene, using a combination of two pairs of conserved primers (e.g.…”
Section: Discussionmentioning
confidence: 62%
“…However, in this study we had similarly high success rates for DNA extraction and PCR amplification for species, sex and individual identification from jaguar faecal samples in two areas with contrasting environmental conditions. Furthermore, species identification rates based on our previously developed method (Roques et al, 2011) were higher (70% for Serra da Capivara National Park and 81% for Caiman Ecological Refuge) than those reported for sequencing methods for faeces of the same species collected in the field (59%, Farrell et al, 2000;55%, Haag et al, 2009). The use of a single pair of Amelogenin-based primers for sex determination also proved to be reliable and a more efficient technique (73-96% success rates) than those previously reported, which were usually based on amplification of the Y-chromosome-linked sexdetermining region gene, using a combination of two pairs of conserved primers (e.g.…”
Section: Discussionmentioning
confidence: 62%
“…Another difficulty in diet studies is that G. cuja builds latrines, often with contribution of scats by several individuals (delibes et al, 2003), impeding study of individual diets. These difficulties can be addressed by collection of fresh scats and use of camera traps and molecular analysis (faRRell et al, 2000), or via studies based on stomach contents of carcasses, considering the relatively frequent cases of road kills of the species (pfeifeR et al, 2008;CáCeRes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For faeces this has involved the sample being dehydrated either by air drying (e.g. pumas and jaguars: Farrell et al 2000;sheep and reindeer: Flagstad et al 1999) or alcohol treatment (e.g. chimpanzees: Constable et al 2001;baboons: Bayes et al 2000;bonobos: Gerloff et al 1999;elephants: Fernando et al 2000), frozen at -20°C (e.g.…”
Section: Methodological Considerations Collection and Storage Of Samplesmentioning
confidence: 99%
“…In another example, assignment of field-collected scats to each of four sympatric Venezuelan carnivore species using mtDNA analysis, indicated that scat size overlapped considerably among species. This produced a much-altered profile of their dietary niches, which had previously been interpreted on the basis of erroneous assumptions about scat size (Farrell et al 2000).…”
Section: Dietary Analysismentioning
confidence: 99%